Communicators competence, intercultural communication, service quality, and international students satisfaction towards administrative staffs of public university in Malaysia - Chinonso, Obasi Johnson (2024)
In this new era, students prefer to study abroad because of its benefits, such as exposure, learning new cultures, and opportunities to meet new friends and interact with them. This has increased the number of international students studying abroad. The acceptance rate of international students studying at public universities in Malaysia is continuously growing, whereas local administrative staff is one of the greatest challenges faced by international students. In the dissatisfaction, misconduct. Grounded in the communication accommodation theory and servqual theory. This study examined the relationship factors that affect international students’s satisfaction with the total performances of local administrative staff at public universities in Malaysia. This study is quantitative research; a questionnaire was developed and an online survey was used. A total of 416 usable responses were received. The statistical package for social science (SPSS version 26) was used for regression analysis data results. The conceptual model revealed a ‘high’ explanatory significant influence on international student’s satisfaction by communicator competence, intercultural communication, and service quality from the local administrative staff of both Universiti Utara Malaysia (UUM) and Universiti Perlis Malaysia (UNIMAP). The findings of this study provide an important insight for general performance on service quality and further enrich the understanding of the effects of local administrative staff on international students’s satisfaction. It is then recommended that public universities in Malaysia, particularly UNIMAP and UUM, encourage their local administrative staffs to exercise proper competence in communication and intercultural exchange towards improving service quality in order to increase international student satisfaction. Finally, the study's implications, suggestions, and recommendations for future research are discussed for the satisfaction of students in general, especially international students at public universities in Malaysia.